Collagen Hydrogels for Regenerative Medicine - Pupkaite, Justina (Université d'Ottawa / University of Ottawa, 2020)
The need for regenerative therapies to repair damaged or deteriorated organs and tissues, such as heart, skin, and cornea, is rising due to donor shortage and aging of the world’s population. Many proposed regenerative therapeutic approaches include a combination of cells, bioactive compounds, and hydrogels. Although collagen hydrogels have shown a lot of promise in regenerative medicine research, there are still challenges in their design and application strategies. Therefore, this thesis describes the development of novel collagen hydrogel designs for improved use in tissue bonding, cell delivery, and myocardial infarction therapy applications. Firstly, a visible-light crosslinked collagen hydrogel for tissue photobonding was developed. Methacrylated collagen hydrogel was crosslinked using the photoinitiator rose Bengal and visible light. The properties of the resulting hydrogel were tunable by changing the hydrogel composition. Biomimetic and ex vivo skin models were used to demonstrate the ability of the hydrogel to bond tissues whose edges are separated. Additionally, using the hydrogel led to less scarring compared to traditional sutures in a mouse skin incision model. Secondly, collagen was modified with thiol groups to design a hydrogel crosslinked using the thiol-Michael addition click reaction for cell encapsulation and delivery. The hydrogels demonstrated excellent shear-thinning and self-healing properties, allowing for injection after the crosslinking was complete. Additionally, the hydrogels showed minimal swelling and maintained their shape in an aqueous buffer for a prolonged period. Cell encapsulation and delivery using the hydrogels was demonstrated in vitro with mesenchymal stromal cells and endothelial cells. Thirdly, recombinant human collagen III hydrogels were prepared by crosslinking the collagen with EDC and NHS. The hydrogels contained either 1% or 2% collagen. Therapeutic strategies for these hydrogels were investigated, including the timing and dosage of the treatment, in a mouse MI model. Comparing 1% hydrogel injection at a single early time point (3 h) and three time points (3 h, 7 and 14 days) post-MI revealed improved cardiac function, reduced scar size and inflammation, and increased vascularization in the single injection group. Additionally, increasing the collagen III dose to 2% in the hydrogel at a single early time point (3 h) injection did not confer any additional functional improvement compared to 1% and resulted in scar size and vascular density comparable to control (PBS injection). In summary, this work contributes to the development of collagen hydrogel therapies for regenerative medicine by presenting a visible-light crosslinked collagen hydrogel for tissue bonding, a novel click-crosslinked collagen hydrogel with excellent shear-thinning properties for cell delivery, and the use of a recombinant human collagen III hydrogel in post-MI therapy, highlighting the importance of optimizing the timing and dosage of biomaterial therapies.
Keywords: Regenerative Medicine; Hydrogel; Collagen; Injectable Hydrogel; Cardiovascular Disease; Tissue Photobonding